2016
DOI: 10.1111/joss.12233
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of perceptual expectation effect based on neural coding principles

Abstract: Prior expectation affects posterior perceptual experience. This contextual bias is called expectation effect. Previous studies have observed two different patterns of expectation effect: contrast and assimilation. Contrast magnifies the perceived incongruity, and assimilation diminishes the incongruity. This study proposes a computational model that explains the conditions of contrast and assimilation based on neural coding principles. This model proposed that prediction error, uncertainty, and external noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Meanwhile, for the responses on "noisy" feeling, expectation effect could not be determined. A previous study suggested that uncertain expectations provide only a small extent of expectation effect (Yanagisawa, 2016a). As assumed, the participants hardly predicted the "noisy" feeling of sound based only on body size.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Meanwhile, for the responses on "noisy" feeling, expectation effect could not be determined. A previous study suggested that uncertain expectations provide only a small extent of expectation effect (Yanagisawa, 2016a). As assumed, the participants hardly predicted the "noisy" feeling of sound based only on body size.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, tolerance decreases. (Yanagisawa, 2016a) found that the pattern of expectation effect shifted from assimilation to contrast as the prediction error (the difference between expected and actual value) by using a computational model of expectation effect. More than certain prediction error causes contrast, whereas small prediction error causes assimilation.…”
Section: Expectation Effect and Tolerance Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms and conditions governing the contrasting and assimilating patterns are not yet clearly elucidated. In this study, I proposed a mathematical model of the expectation effect that explains the conditions of contrast and assimilation by applying neural coding principles, such as Bayesian decoding and the efficient encoding principles [1]. Based on the proposed model, I conducted computer simulations of the expectation effect and obtain an accurate hypothesis of the conditions of assimilation and contrast.…”
Section: Introductionmentioning
confidence: 99%
“…The role of higher-level cognitive factors (e.g., consumer expectations) should also be considered . It has been argued that under the appropriate conditions, both sensory congruency and sensory incongruity between what is expected and what is experienced while tasting can bring positive or negative reactions to the overall tasting experience Yanagisawa, 2016). Visual cues (particularly color) set sensory and hedonic expectations regarding the likely taste and flavor properties of food and drink items.…”
Section: Introductionmentioning
confidence: 99%